Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Les Principes De Jogjakarta: Principes sur l'application de la législation internationale des droits humains en matière dórientation sexuelle et d'identité de genre (2006)
Principes additionnels et obligations additionnelles des états au sujet de l’application du droit international des droits humains en matière d’orientation sexuelle, d’identité de genre, d’expression de genre et de caractéristiques sexuelles pour completer les Principes de Jogjakarta Depuis leur adoption en 2006, les Principes de Jogjakarta ont évolué pour devenir une déclaration faisant autorité sur les droits humains des personnes « d’orientations sexuelles et d’identités de genre diverses ». La dernière décennie a été témoin de développements significatifs dans le domaine du droit international des droits humains, ainsi que dans la compréhension des violations des droits humains subies par les personnes « d’orientations sexuelles et d’identités de genre diverses », et dans la reconnaissance des violations souvent distinctes touchant des personnes en raison de leur « expression de genre » ou de leurs « caractéristiques sexuelles ».Les Principes de Jogjakarta plus 10 (PJ+10) visent à documenter et à détailler ces développements à travers un ensemble de Principes additionnels et d’Obligations additionnelles des États.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; antiracisme; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; outils; pol4022; premier cycle; périodes historiques; queer; racisme; régions géographiques; science politique; sud global; systèmes d'oppressions; thématiques

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Women artists at the millennium - Armstrong, Carol M.; Zegher, M. Catherine de (MIT Press, 2006)
"More than thirty years after the birth of the modern women's movement and the beginnings of feminist art-making and art history, the time is ripe to examine the legacies of those revolutions. In Women Artists at the Millennium, artists, art historians, and critics examine the differences that feminist art practice and critical theory have made in late twentieth-century art and the discourses surrounding it. In 1971, when Linda Nochlin published her essay "Why Have There Been No Great Women Artists?" in a special issue of Art News, there were no women's studies, no feminist theory, no such thing as feminist art criticism; there was instead a focus on the mythic figure of the great (male) artist through history. Since then, the "woman artist" has not simply been assimilated into the canon of "greatness" but has expanded art-making into a multiplicity of practices with new parameters and perspectives. In Women Artists at the Millennium artists including Martha Rosler and Yvonne Rainer reflect upon their own varied practices and art historians discuss the innovative work of such figures as Louise Bourgeois, Lygia Clark, Mona Hatoum, and Carrie Mae Weems. And Linda Nochlin considers changes since her landmark essay and looks to the future, writing, "We will need all our wit and courage to make sure that women's voices are heard, their work seen and written about."--Jaquette
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; art féministe; corps; cours; discours dominant; femmes* artistes; har4600; maternité; premier cycle; périodes historiques; représentation; sexisme; systèmes d'oppressions; thématiques

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

Comment devient-on homo ou hétéro? - Clerget, Stéphane (JC Lattès, 2006)
Le pédopsychiatre présente les découvertes récentes de la psychanalyse, la neurobiologie, la génétique, l'histoire, la sociologie, etc., à propos de la construction de l'identité sexuelle et de la part d'inné et d'acquis dans la définition des préférences sexuelles.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

S’approprier son corps et sa santé. Entretien avec Rina Nissim - Fussinger, Catherine; Rey, Séverine; Vuille, Marilène (Nouvelles Questions Feministes, 2006)
Parmi les personnes qui ont réellement fait avancer les choses et apporté des changements dans la vie de beaucoup de femmes, il y a Rina Nissim qui a oeuvré depuis son engagement au sein du MLF de Genève au début des années 1970 pour que les femmes se réapproprient leur corps et leur santé. Ce numéro de « Nouvelles Questions féministes » sur la santé consacre une bonne partie de ses pages à une discussion avec Rina Nissim. Cette militante du groupe « avortement » et self-help » du MLF genevois raconte comment elle est passée de l'école d'infirmière à une vie de militantisme et de voyages, avec la naturopathie pour bagage. Publiant des ouvrages sur la santé des femmes ayant eu un succès important tel que « Mamamélis », cette pionnière en Suisse ouvre le « dispensaire des femmes »fonctionnant sur un mode autogéré, suite à un voyage aux États-Unis, avec d'autres femmes infirmières psychologues et médecins. Les femmes vont alors trouver une alternative aux rapports de pouvoirs classiques des relations médecin-patient et aux médicaments traditionnels, dans un mouvement de prise de conscience et d'action sur leur propre corps. L'engagement international de Rina, en Amérique Central et en Inde principalement où elle s'installe cinq ans et coordonne différents projets, aura permis a de nombreuses femmes de se découvrir elles-mêmes et les autres, de se débarrasser de la honte et se rendre compte que la maladie est souvent liée à un positionnement social.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; europe; france; inde; justice reproductive; premier cycle; périodes historiques; racisme; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail; états-unis

La sexualité entre sexisme et racisme: les descendantes de migrant·e·s du Maghreb et la virginité - Hamel, Christelle (Nouvelles Questions Féministes, 2006)
L'article présente le résultat d'une recherche sur la vie affective et sexuelle des jeunes Français-es descendant de migrant-e-s originaires du Maghreb, qui décrit comment les jeunes femmes se positionnent par rapport au principe de virginité. Alors que cette norme est un mode de contrôle de la sexualité des femmes, certaines le revendiquent, tandis que celles qui l'ont transgressé expriment combien cette décision leur fut difficile. Pour comprendre la prégnance de leur attachement à la valeur de la virginité, l'autrice replace leurs discours et pratiques dans le contexte social qui les a fait naître. Elle décrit donc comment les discriminations et la stigmatisation racistes façonnent l'expérience de vie de ces jeunes femmes et montre combien cette expérience du racisme se combine à l'expérience du sexisme dans les familles et dans la société globale. Ici, l'imbrication du sexisme et du racisme fait peser sur elles un système de contraintes complexe qui les soumet à des injonctions paradoxales. Ce n'est qu'au regard de ces injonctions que la revendication par certaines de cette norme qui par ailleurs les opprime devient intelligible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; intersectionnalité; maghreb; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; virginité; études démographiques

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Médicalisation de la ménopause, mouvements pour la santé des femmes et controverses sur les thérapies hormonales - Löwy, Ilana; Gaudillière, Jean-Paul (Nouvelles Questions Feministes, 2006)
Le traitement hormonal de la ménopause, présenté entre 1970 et 2000 par la majorité des experts comme capable d’accroître le bien-être des femmes mais aussi de prévenir des nombreuses pathologies liées au vieillissement féminin, a été déclaré en 2002 inutile et dangereux suivant un essai clinique nord américain, Women’s Health Initiative (WHI). En voie de conséquence, les prescriptions de ce traitement ont chuté dramatiquement entre 2002 et 2005. Cet article retrace les origines féministes de WHI, puis suit les conséquences de la publication de ses résultats aux États-Unis, en France et en Allemagne. En conclusion, il revient sur les tensions entre les rôles des femmes comme utilisatrices des hormones, comme expertes et comme militantes des mouvements pour la santé des femmes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; allemagne; amérique du nord; amériques; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Femmes et immigrées: corvéables à merci - Puech, Isabelle (Travail, genre et sociétés, 2006)
Dans le secteur des services, des milliers de femmes connaissent des formes d’exploitation salariale diffuses, peu visibles, socialement tolérées. Cet article propose de mettre en lumière un mode de gestion de la main-d’œuvre non qualifiée qui, sous couvert de flexibilité et de compression maximale des coûts, utilise les femmes les plus vulnérables sur le marché du travail – en particulier les femmes immigrées – comme variable d’ajustement. À partir d’une enquête de terrain menée auprès d’une population de femmes de chambre, l’article s’attachera à mettre au jour une face cachée des emplois précaires. Des emplois souvent à durée indéterminée qui ne protègent pas des conditions de travail pénibles, des temps de travail à rallonge, des salaires au rabais et des pratiques patronales frauduleuses.
Keywords: 1900-1999; 1970-1979; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; afrique subsaharienne; approches et analyses; capitalisme racial; corps; cours; discipline; europe; france; inégalités; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions--racism and Islamophobia--in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques